2015
DOI: 10.1089/cyber.2013.0690
|View full text |Cite
|
Sign up to set email alerts
|

Using a Digital Game for Training Desirable Behavior in Cognitive–Behavioral Therapy of Burnout Syndrome: A Controlled Study

Abstract: Using a digital game for training desirable behavior in cogrnitive-behavioral therapy for burnout syndrome: a controlled study Zielhorst, T.; van den Brule, D.; Visch, V.; Melles, M.; van Tienhoven, S.; Sinkbaek, H.; Schrieken, B.A.L.; Tan, E.S.H.; Lange, A. Published in:Cyberpsychology, Behavior, and Social Networking DOI:10.1089/cyber.2013.0690 Link to publicationCitation for published version (APA): Zielhorst, T., van den Brule, D., Visch, V., Melles, M., van Tienhoven, S., Sinkbaek, H., ... Lange, A. (2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 51 publications
0
22
0
2
Order By: Relevance
“…As can be seen in Figure 2, the five studies focused on physical activity [27,32,34,36,37] represent a third of the total, and the five focused on life purpose studies [28,30,35,39,40] represent another third. Four of the studies related to the “life purpose” pillar [30,32,41,42] (80% of the “life purpose” pillar related studies and 26.66% of the total of studies) focus on habit management and CBT. Only two of the studies [36,40], which represent 13.33%, are multimodal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen in Figure 2, the five studies focused on physical activity [27,32,34,36,37] represent a third of the total, and the five focused on life purpose studies [28,30,35,39,40] represent another third. Four of the studies related to the “life purpose” pillar [30,32,41,42] (80% of the “life purpose” pillar related studies and 26.66% of the total of studies) focus on habit management and CBT. Only two of the studies [36,40], which represent 13.33%, are multimodal.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the classification of studies according to how they monitor subjects. Eight of the studies identified (53.33%) [30,31,32,33,35,37,40,41] employed light monitoring, based on questionnaires and tests to get data and parameters from users. Three of the studies [29,36,39] (20%) employed heavy monitoring with controlled spaces or specific devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using CBT, ''Dealing with Others,'' when combined with therapy, was found to improve coping skills for burnout syndrome more than therapy alone. 66 ''Dealing with Others'' trains individuals to assertively communicate with coworkers and offers positive thoughts about themselves or society. Difficulty levels increase as players gather points.…”
Section: Current Games For Mental Disordersmentioning
confidence: 99%
“…stress, which supports their occupational nature. (3,4,5) Medical students are continually exposed to stressors such as: adaptation difficulties, excessive workload and / or studies and lack of leisure time which, if persistent, may trigger the syndrome. These factors are potentially responsible for several psychosocial changes that lead to the development of anxiety and depression, which can lead to suicide.…”
Section: Introductionmentioning
confidence: 99%